Lifestyle in Siberia and the Russian North - Habeck, Joachim Otto (Open Book Publishers, 2019)
"Lifestyle in Siberia and the Russian North breaks new ground by exploring the concept of lifestyle from a distinctly anthropological perspective. Showcasing the collective work of ten experienced scholars in the field, the book goes beyond concepts of tradition that have often been the focus of previous research, to explain how political, economic and technological changes in Russia have created a wide range of new possibilities and constraints in the pursuit of different ways of life. Each contribution is drawn from meticulous first-hand field research, and the authors engage with theoretical questions such as whether and how the concept of lifestyle can be extended beyond its conventionally urban, Euro-American context and employed in a markedly different setting. Lifestyle in Siberia and the Russian North builds on the contributors' clear commitment to diversifying the field and providing a novel and intimate insight into this vast and dynamic region. This book provides inspiring reading for students and teachers of Anthropology, Sociology and Cultural Studies and for anyone interested in Russia and its regions. By providing ethnographic case studies, it is also a useful basis for teaching anthropological methods and concepts, both at graduate and undergraduate level. Rigorous and innovative, it marks an important contribution to the study of Siberia and the Russian North."